Limit behavior of some quadratic stochastic operators on segment [0,1] - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (2015)
In this paper, we construct some class of quadratic stochastic operator defined on continual state space [0,1], and show that such operators are regular transformation